(untitled) (REMUNOM, 2025)
This study critically analyzes teacher training for cultural diversity in public schools, from the perspective of continuing and reflective training. Based on a state-of-the-art study that examined publications in national journals classified in the upper strata of Qualis/CAPES and papers presented at the annual meetings of ANPEd in the early 21st century, trends, emphases, and silences in academic production on multiculturalism, identity, difference, and educational equity are identified. The research shows that, despite theoretical advances in the field of critical and postcolonial multiculturalism, there is still a shortage of research that consistently articulates such references to the continuing education of teachers in the daily life of public schools. There is a predominance of descriptive approaches, focused on specific collective identities, to the detriment of analyses situated in the “school environment” and studies that address cultural hybridization, institutional identity, and multicultural pedagogical practice. The results suggest the need to strengthen training models that integrate action research, teacher reflection, and culturally responsive curricular practices, expanding the capacity of schools to respond to Brazil’s cultural plurality. The article concludes with recommendations for advancing the field, advocating for continuing education policies and programs that incorporate critical, postcolonial, and social justice perspectives.